SOCIAL SUPPORT AND ACADEMIC RESILIENCE IN ONLINE LEARNING DURING PANDEMIC - SRI WIYANTI; WAHYU SAEFUDIN; SITI HAJAR BINTI MOHAMAD YUSOFF (Universitas Islam Negeri Mataram, 2021)
The pandemic has implications for policy changes in Indonesia, especially in the field of education. Face-to-face learning is then transformed into online learning through learning from home policies. Unfortunately, online learning carried out by students has various challenges, so academic resilience is needed. This study aims to analyze how students own academic resilience and how social support performs a role in online learning. This study utilizes a literature study approach by collecting data from various journals, government websites, books, and appropriate references. The analysis results explain that the academic resilience of students in online learning during the pandemic is at the lower middle level. This level means that students cannot maximize online learning during a pandemic. Furthermore, social support variables enhance students’ academic resilience so that social support through various sources will affect students’ academic success during online learning.